A Model For Long Range Scheduling Of The Mining Sequence For Flat Lying Orebodies - R. Gerling (Society for Mining, Metallurgy & Exploration, 1986)
A computer program has been developed for finding a near-optimum schedule of the mining sequence for flat lying, tabular orebodies. The deposit is divided in blocks with equal areas and definite grades, thicknesses and ore contents. Mining is done by room and pillar method and trackless haulage to surface. Access from surface is by adits or ramps with additional vent raises. In total eight different general concepts for access and development can be realized. The optimum mining sequence is found by a heuristic method. Criterion is the maximization of the net present value over the lifetime of the mine. Specific stoping costs per t of ore are taken for con¬stant, whereas development and haulage costs for individual blocks and also sequences will be different. Correct ventilation and a technically sensible sequence are guaranteed. Beginning with a single block, neighbouring blocks are tested and an optimum stoping sequence is generated. The net present value of the total mining operation for the planning period is calculated, taking into account ore, which is mined during development. The program can also be used to investigate given mining sequences.